2016
DOI: 10.1371/journal.pone.0153885
|View full text |Cite
|
Sign up to set email alerts
|

Non-Heme Iron Absorption and Utilization from Typical Whole Chinese Diets in Young Chinese Urban Men Measured by a Double-Labeled Stable Isotope Technique

Abstract: BackgroundThis study was to observe the non-heme iron absorption and biological utilization from typical whole Chinese diets in young Chinese healthy urban men, and to observe if the iron absorption and utilization could be affected by the staple food patterns of Southern and Northern China.Materials and MethodsTwenty-two young urban men aged 18–24 years were recruited and randomly assigned to two groups in which the staple food was rice and steamed buns, respectively. Each subject received 3 meals containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…This proportion, which we called the circulating rate, was actually equal to the erythrocyte incorporation rate mentioned in other studies because the formulas were to calculate the ratio of 58 Fe in the blood compared to the 58 Fe administrated. In the article published by our group in 2016 [ 20 ], the 58 Fe incorporation rate of males was 85%, consistent to our rate of 85.46%. While in this paper, the concentration of total iron in blood was measured by AAS, which might be more accurate than previous studies using hemoglobin concentration as an estimate.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This proportion, which we called the circulating rate, was actually equal to the erythrocyte incorporation rate mentioned in other studies because the formulas were to calculate the ratio of 58 Fe in the blood compared to the 58 Fe administrated. In the article published by our group in 2016 [ 20 ], the 58 Fe incorporation rate of males was 85%, consistent to our rate of 85.46%. While in this paper, the concentration of total iron in blood was measured by AAS, which might be more accurate than previous studies using hemoglobin concentration as an estimate.…”
Section: Discussionsupporting
confidence: 90%
“…By monitoring the first 14 days, our team obtained the absorption rate and the red cell utilization rate of non-heme iron, and the results of male have been published. Specific diet recipes and the preparation of isotopically labeled iron have also been described in detail in the previous article [ 20 ]. The women and men underwent the same procedure in this study, while the current article on women has not yet been published.…”
Section: Methodsmentioning
confidence: 99%
“…The main long-term strategy to solve this problem is food fortification. However, the proportion of iron that is absorbed and used in normal body functions (iron bioavailability) is strongly influenced by dietary components (Bryszewska et al, 2019;Yang et al, 2016). In this regard, non-heme iron can interact with several food components during gastrointestinal digestion and form complexes, which can increase or decrease mineral absorption (Lazarte, Carlsson, Almgren, Sandberg, & Granfeldt, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The iron circulation rate in women of reproductive age was 80.4%, which has no significant difference with the result 82.8% in our previous study [20], and was close to that in other studies. In the article published by our team in 2016, the 58 Fe incorporation rate of males was 85% [25]. Hiroshi Saito et al in 1964 reported that the average utilization radio of iron was 90, and 10% remained in tissues of 12 men [18].…”
Section: Discussionmentioning
confidence: 99%